“Fé, oração e atividade”: a inserção da Igreja Episcopal Brasileira no campo religioso santa-mariense a partir das estratégias de missionários e leigos (1899-1906) - Vianna, Paulo Henrique Silva (2019)
This work addresses the union of strategies used by clergy and laypeople in the daily missionary work of the Brazilian Episcopal Church in the central region of the State of Rio Grande do Sul, in the city of Santa Maria. Information found in the administrative records kept by the parish vestry and the Women's Auxiliary Society identify the objectives, choices and decisions responsible for the maintenance, permanency and development of missionary work. The presence of the clergy in the religious field of Santa Maria and their work distributing symbolic religious goods resulted in the migration of people to the interior of the Episcopal Church and the expansion of missionary work in nearby towns, including Vila Rica and Restinga Seca. Among the work developed by the priests and laypeople, the construction process of the Cathedral Mediador, inaugurated in November of 1906, is highlighted as an event which represents the mobilization capacity of the religious community and its formulation of strategies. Regarding the activities developed by the laypeople, the Women's Auxiliary Society was prominent and evidenced the work of women in the management of material and symbolic values. The research was also able to identify ties of solidarity and camaraderie between the protestant missionaries and social groups critical to the Roman Catholic Church. From what we could explore, the pattern of cooperation existed between protestant agents, Masons and anticlerics in the city. As general guidelines, we used the process of modernization through which Brazilian society underwent in the 19th century and the construction of religious to elaborate this narrative. The research is part of the research line Culture, Migrations and Work, of the Graduate Program in History of the Federal University of Santa Maria (PPGH-UFSM), at the master's level, and counted on the assistance of the CAPES / DS grant.